2015
DOI: 10.1002/bsl.2189
|View full text |Cite
|
Sign up to set email alerts
|

Double Parricide: An In‐Depth Look at Two Victim Homicides Involving Parents as Victims

Abstract: The majority of studies examining the killing of parents and step-parents by biological and stepchildren involve a single victim and single offender. Little is known when parricide incidents involve multiple victims or multiple offenders. Using the National Incident-Based Reporting System (NIBRS), this study examined double parricide incidents involving single or multiple offenders over the 20-year period 1991-2010 with the aim of investigating juvenile and adult involvement. Forty-five incidents of double par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In this study, the murders were predominantly committed by male offenders, as was also found in the literature (Barnett, Miller-Perrin, & Perrin, 2011; Fegadel & Heide, 2015). The offenders in this study all lived with the murdered family member(s) at the time of the murders; this was often reported in the literature as well (Dantas et al, 2014).…”
Section: Findings and Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In this study, the murders were predominantly committed by male offenders, as was also found in the literature (Barnett, Miller-Perrin, & Perrin, 2011; Fegadel & Heide, 2015). The offenders in this study all lived with the murdered family member(s) at the time of the murders; this was often reported in the literature as well (Dantas et al, 2014).…”
Section: Findings and Discussionsupporting
confidence: 77%
“…Family murders are predominantly committed by single perpetrators with a single victim (Fegadel & Heide, 2015). When women commit these crimes, they often have an accomplice (Heide, 1993).…”
Section: Children Who Commit Family Murdermentioning
confidence: 99%
See 1 more Smart Citation
“…However, almost a third of parricides that involve multiple offenders involve females as the ‘principal offender’, and there is a significant relationship between the offenders’ gender and whether other offenders are involved. In the United States, where similar findings have emerged (Heide, 2013), analysis of the corresponding news reports suggests that girls and women may be more likely to recruit boyfriends and partners to help them carry out the killing of their parent (Fegadel and Heide, 2015).…”
Section: Findings: Parricide In England and Wales (1977–2012)mentioning
confidence: 77%
“…Indeed, the three national data sets available in the United States (the Uniform Crime Report (UCR), Supplementary Homicide Reports (SHR), and National Incident‐Based Reporting System (NIBRS)) do not contain codes for adoption when describing the offender to victim relationship. Therefore, much of what is known about parricide is limited to biological children who have killed their parents or stepparents (Fegadel & Heide, ; Heide, , , , ).…”
Section: Introductionmentioning
confidence: 99%